1995
DOI: 10.1128/jb.177.8.1989-1993.1995
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of biodegradation of metal-citrate complexes by Pseudomonas fluorescens

Abstract: Biodegradation of metal-citrate complexes by Pseudomonas fluorescens depends on the nature of the complex formed between the metal and citric acid. Bidentate Fe(III)-, Ni-, and Zn-citrate complexes were readily biodegraded, but the tridentate Cd-and Cu-citrate, and U-citrate complexes were not. The biodegradation of Ni-and Zn-citrate commenced after an initial lag period; the former showed only partial (70%) degradation, whereas the latter was completely degraded. Uptake studies with 14 C-labeled citric acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 30 publications
2
67
1
Order By: Relevance
“…MBR were similar to that by Pseudomonas fluorescens [7,8,15] [7]. Therefore, the non-biodegradable tridentate Fe(III)-citrate complex was the predominant complex in the 1:1 Fe:citrate medium at pH Table 2 Distribution and uptake of metals in Pseudomonas sp.…”
Section: Biodegradation Of Fe(iii)- Zn-and Cd-citrate Complexmentioning
confidence: 85%
See 1 more Smart Citation
“…MBR were similar to that by Pseudomonas fluorescens [7,8,15] [7]. Therefore, the non-biodegradable tridentate Fe(III)-citrate complex was the predominant complex in the 1:1 Fe:citrate medium at pH Table 2 Distribution and uptake of metals in Pseudomonas sp.…”
Section: Biodegradation Of Fe(iii)- Zn-and Cd-citrate Complexmentioning
confidence: 85%
“…Bidentate complexes, such as Fe(III)-and Zn-citrate can be transported as intact complex inside the bacteria and then was biodegraded [7]. Tridentate and binuclear complexes, such as Cd-and U-citrate are recalcitrant to biodegradation due to the lack of transport systems for metal-citrate complexes or the inability of the citrate degrading enzymes to utilize the complexes as substrate or both [8].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the metabolism of the metal-citrate complex is dependent upon the type of complex formed between the metal and citric acid. Fe(III) forms a bidentate complex with citric acid and was metabolized, whereas U forms a binuclear complex with citric acid and was recalcitrant (Francis et al 1992;Francis and Dodge,1993;Joshi-Tope and Francis 1995). The resting cells of the sulfate-reducing Desulfovibrio desulfuricans and the facultative iron-reducing Shewanella halotolerans bacteria reduced U(VI) complexed with oxalate or citrate to U(IV) under anaerobic conditions with little precipitation of uranium.…”
Section: Biotransformation Under Anaerobic Conditionsmentioning
confidence: 99%
“…The Mg 2+ -citrate transporter CitM of Bacillus subtilis is the best-studied example and accepts the toxic heavy metal ions Zn 2+ , Ni 2+ and Co 2+ instead of Mg 2+ in the metal-citrate complex . Bacteria capable of taking up and metabolizing heavy metal ions complexed to citrate have been implicated in preventing the mobilization of toxic metals from waste dumps (Joshi-Tope and Francis 1995). Alternatively, these organisms may play a role in bioremediation of heavy-metal-polluted sites by active accumulation of the toxic ions after heterotrophic leaching with citrate (White et al 1997;Peters 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of bacteria of the genera Pseudomonas, Citrobacter, Bacillus and Klebsiella have been described that transport metal-citrate complexes across the cytoplasmic membrane into the cell (Willecke et al 1973;Bergsma and Konings 1983;Madsen and Alexander 1985;Brynhildsen and Rosswall 1989;Joshi-Tope and Francis 1995). The Mg 2+ -citrate transporter CitM of Bacillus subtilis is the best-studied example and accepts the toxic heavy metal ions Zn 2+ , Ni 2+ and Co 2+ instead of Mg 2+ in the metal-citrate complex .…”
Section: Introductionmentioning
confidence: 99%